2008
DOI: 10.1158/0008-5472.can-08-0482
|View full text |Cite|
|
Sign up to set email alerts
|

The Chemokine Receptor CXCR6 and Its Ligand CXCL16 Are Expressed in Carcinomas and Inhibit Proliferation

Abstract: The chemokine receptor CXCR6 and its ligand CXCL16 are involved in inflammation. Thus far, they were known to be expressed mainly by T cells and macrophages, respectively. However, we detected both in all of 170 human primary mammary carcinomas and at similar levels in all 8 human mammary carcinoma cell lines tested by microarray analysis. Expression was confirmed by reverse transcription-PCR and for the cell lines also by fluorescence-activated cell sorting analysis. CXCR6 and CXCL16 were also detected in sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 48 publications
1
36
0
Order By: Relevance
“…CXCL16 is a ligand for CXCR6, a member of the seven transmembrane G protein-coupled receptor family, and signals through the Akt pathway (Meijer et al 2008). Independent of macrophages, the CXCL16-CXCR6 complex has been shown to promote cancer proliferation or metastasis in prostate (Lu et al 2008, Jung et al 2013, renal (Gutwein et al 2009), and pancreatic (Wente et al 2008) cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CXCL16 is a ligand for CXCR6, a member of the seven transmembrane G protein-coupled receptor family, and signals through the Akt pathway (Meijer et al 2008). Independent of macrophages, the CXCL16-CXCR6 complex has been shown to promote cancer proliferation or metastasis in prostate (Lu et al 2008, Jung et al 2013, renal (Gutwein et al 2009), and pancreatic (Wente et al 2008) cancer.…”
Section: Discussionmentioning
confidence: 99%
“…One of the unidentified issues in the role of CXCL16 signaling in cancers is on the functional divergence of two different types of CXCL16 proteins: soluble and trans-membrane forms. Meijer et al (2008) showed that the two types of CXCL16 had different roles in cell proliferation and metastasis, and a certain model suggested that the soluble CXCL16 induces cancer cell proliferation and metastasis (Deng et al 2010), while the trans-membrane CXCL16 suppressed it. However, it is still unclear and needs to be redefined according to specific tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the only CXCL lower expressed in ATM was CXCL16, also involved in leukocyte migration and adhesion (38). Importantly, high expression levels of CXCL16 in renal cancer tissue has been correlated with a better survival rate of patients (39,40). Our study also reveals that circulating levels of Gro (CXCL1, -2, -3), CXCL9, -10, -11 (CXCR3 ligands), and sgp130, key players in the maintenance and amplification of autoimmunity-related inflammatory processes (35), are elevated in obese subjects, whereas anti-proliferative TGF␤1 concentrations are lower (41).…”
Section: Discussionmentioning
confidence: 99%
“…In human glioma, colorectal, breast and renal cancer, tumors with high CXCL16 expression had slower progression and showed infiltration of CD4 and CD8 lymphocytes [53][54][55][56][57]. On the contrary in prostate cancer CXCL16 expression has been correlated with poor prognosis [58].…”
Section: Chemokine Regulation Of Leukocyte Attraction Within Tumorsmentioning
confidence: 99%